Carbon Isotope Discrimination (δ13 C) of Grape Musts Is a Reliable Tool for Zoning and the Physiological Ground-Truthing of Sensor Maps in Precision Viticulture - Brillante, Luca; Martínez-Lüscher, Johann; Yu, Runze; Kurtural, Sahap Kaan (Frontiers in Environmental Science, 2020)
Carbon stable isotope composition of berry must at harvest (δ13C) is an integrated assessment of plant water status during grape (Vitis vinifera L.) berry ripening. Measurement of δ13C of grape juice is proposed as an alternative to traditional measurements of water status to capture the spatial variability of physiological response at the vineyard scale, i.e. zoning. We performed samplings at four different locations in California, USA, with three different cultivars of table and wine grapes (Cabernet Sauvignon, Merlot, Crimson-Seedless). Leaf physiology (photosynthesis, AN, stomatal conductance, gs) and stem water potentials (Ψstem) were routinely measured. The δ13C was measured at harvest and strong relationships were found between Ψstem (R2 = 0.71), stomatal conductance (R2 = 0.71), net carbon assimilation (R2 = 0.59) and WUEi (R2 = 0.53). The role of leaf nitrogen on the signal was assessed by evaluating relationships between leaf nitrogen and WUEi (R2 = 0.54), Ci/Ca (R2 = 0.51), δ13C (R2 = 0.44), and Ψstem (R2 = 0.37). Although nitrogen can be among the environmental factors able to affect the δ13C signal, this difference is only observable when variability in N is very large, by pooling different vineyards/varieties, but not at the within-vineyard scale. The utility of δ13C was further tested and measured on grape berries sampled on an equidistant grid in a 3.5 ha vineyard where Ψstem was also measured throughout the field season and used to delineate management zones. Physiological measurements and grape composition were correlated to soil electrical resistivity and satellite-derived vegetation index. The two management zones obtained by δ13C or Ψstem were spatially similar at 67% and allowed to separate the harvest in two pools having statistically different grape composition (soluble solids, organic acids, and anthocyanin profiles). Zoning by δ13C performed as well as zoning by Ψstem to separate grape phenolic composition, e.g. for selective harvest. Our results provided evidence that δ13C of grape must is a reliable and repeatable assessor of plant water status and gas exchange in vineyard systems that are crucial for zoning vineyards, even when irrigated, and for ground-truthing sensor maps in precision viticulture.